Creative Critical Thinking Skill Reviewed by Curiosity on Independent Learning Assisted by E-Learning - Mulyati, Sri; Junaedi, Iwan; YL, Sukestiyarno (Universitas Negeri Semarang, 2021)
This research aims to find out mathematics creative thinking skill of students on independent learning assisted by E-learning. This mixed method used sequential explanatory design. There were 32 subjects of VIII C of Public JHS 1 Bodeh selected by high, moderate, and low Curiosity categories. The techniques of collecting quantitative data were creative thinking skill test and curiosity questionnaire. Technique of collecting qualitative data was done by interview based on curiosity questionnaire and critical thinking skill test result. The findings showed that creative thinking skill pattern reviewed by curiosity realized into high, moderate, and low variety categories. It was shown by six high curiosity students, 3 students whom equal creative level patterns. They met four indicators, such as fluency, reliability, originality, and elaboration. One student met fluency indicator. One student met reliability indicator and originality. One student met reliability and elaboration indicators. The same thing goes for moderate curiosity. There were 20 students. For of them had patterns which met four indicators, 6 of them met 3 indicators, 7 of them met two indicators, 2 of them met one indicator, and 1 of them did not meet any creative thinking skill indicators. There were six students with low curiosity whom had 2 patterns which met three indicators, 2 met two indicators, and 2 students did not meet creative thinking skill indicators.